2016
DOI: 10.1177/0960327115619770
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity assessment of hydroxyapatite nanoparticles in rat liver cell model in vitro

Abstract: Hydroxyapatite nanoparticles (HAP NPs) are widely used for preparations of biomedical and biotechnological fields such as drug delivery, gene therapy, and molecular imaging. However, the current toxicological knowledge about HAP NPs is relatively limited. The present study was designed to investigate the toxicity potentials of various concentrations (0–1000 µg cm−2) of HAP NPs in cultured primary rat hepatocytes. Cell viability was detected by 3-(4,5-dimethyl-thiazol-2-yl) 2,5-dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 53 publications
3
12
1
1
Order By: Relevance
“…Some 2D studies have shown that nodules, which have apoptotic cores, form in response to osteogenic stimuli[23,71]. However, our 3D study reveals that not only were the particles at our dosage not cytotoxic[7274], there was very little apoptosis-driven calcification of the collagen gels, indicating that calcium accumulation within the gel was instead occurring through myofibroblastic activation and osteogenic differentiation mechanisms.…”
Section: Discussionmentioning
confidence: 67%
“…Some 2D studies have shown that nodules, which have apoptotic cores, form in response to osteogenic stimuli[23,71]. However, our 3D study reveals that not only were the particles at our dosage not cytotoxic[7274], there was very little apoptosis-driven calcification of the collagen gels, indicating that calcium accumulation within the gel was instead occurring through myofibroblastic activation and osteogenic differentiation mechanisms.…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, iron depletion has also been shown to reduce guanosine oxidation [77]. Eventually, recent works have substantiated that other stimuli affect 8-oxo-dG content independently of their redox effect, such as carbon tetrachloride [78], forms of graphene [79], diesel exhaust particles or hydroxyapatite nanoparticles [80].…”
Section: Modeling the Fluxes Of H2o2 And •Oh Forming 8-oxo-dgmentioning
confidence: 99%
“…Using a model of cultivated hepatocytes, Sonmez et al [84] evaluated the several potential toxic and genotoxic effects of HA nanoparticles (NPs). With regard to genotoxicity, they evaluated the rate of the liver and measured the levels of 8-oxo-2-deoxyguanosine (8-OH-dG).…”
Section: Biocompatibility Assessment Of Cap-based Bioceramicsmentioning
confidence: 99%